The characteristics of railway service disruption: implications for disruption management. Issue 3 (4th March 2017) - Golightly, D.; Dadashi, N.
Abstract: Rail disruption management is central to operational continuity and customer satisfaction. Disruption is not a unitary phenomenon – it varies by time, cause, location and complexity of coordination. Effective, user-centred technology for rail disruption must reflect this variety. A repertory grid study was conducted to elicit disruption characteristics. Construct elicitation with a group of experts ( n = 7) captured 26 characteristics relevant to rail disruption. A larger group of operational staff ( n = 28) rated 10 types of rail incident against the 26 characteristics. The results revealed distinctions such as business impact and public perception, and the importance of management of the disruption over initial detection. There were clear differences between those events that stop the traffic, as opposed to those that only slow the traffic. The results also demonstrate the utility of repertory grid for capturing the characteristics of complex work domains. Practitioner Summary: The aim of the paper is to understand how variety in rail disruption influences socio-technical design. It uses repertory grid to identify and prioritise 26 constructs, and group 10 disruption types, identifying critical factors such as whether an incident stops or merely slows the service, and business reputation.